Retrospective study of human Brucellosis trends Between 2014-2023 and consideration of One Health perspectives of healthcare professionals in Isiolo County, Kenya - Van Heerden, Henriette (University of Pretoria, 2025)
Mini Disseration (MSc (Global One Health))--University of Pretoria, 2025.